Raw Cured Poultry Meat Fortified with Bee Pollen: Biomedical Research on Laboratory Animals - Maksim A. Sukhov; Tatiana M. Giro; Sergey V. Kozlov; Irina V. Ziruk (Техника и технология пищевых производств)
Natural food additives can fortify meat products. Bee pollen, also known as beebread or ambrosia, contains amino acids, carbohydrates, vitamins, minerals, enzymes, etc. As a result, it possesses numerous therapeutic and prophylactic properties. Bee pollen has good prospects as a fortifying agent for jerky meat, i.e., lean and dehydrated trimmed meat cut into strips. This study tested dry-cured jerky meat fortified with bee pollen on rats with carbon tetrachloride-induced acute toxic hepatitis. The research featured white non-linear laboratory rats. The control group obtained a standard diet. The experimental rats were induced with liver hepatitis by administering CCl4 . On day 2, the experimental group was divided into three subgroups: experimental group I (standard diet + traditional jerky), experimental group II (standard diet + jerky fortified with bee pollen), and experimental group III (standard diet), which served as positive control. The research involved a MicroCC20Vet analyzer for hematological tests and a StatFax 3300 analyzer with Diacon DS diagnostic systems for biochemical tests. The histological analyses relied on the method developed by G.A. Merkulov. The hematological parameters demonstrated no changes. As for the biochemistry, experimental groups I and II developed a protein content increase. On day 14, the concentration of protein and its fractions in experimental group II reached the level of intact animals. In experimental groups II and III, the total protein was significantly higher due to the globulin fraction as a result of inflammatory and destructive processes in the liver. However, the rats had normal live weight gain, and their liver demonstrated no histological deviations. In this preclinical study, bee pollen as part of jerky meat formulation had no negative effect on laboratory rats. Bee pollen also proved its antioxidant properties.